The relationship between food appearance, taste, and serving timeliness and patient food waste at Dr. Abdoer Rahem Regional Hospital, Situbondo - Galih Purnasari; Safin Ratna Andriyani (Ikatan Sarjana Gizi Indonesia (ISAGI), 2026)
The acceptability of hospital food is reflected by the amount of food waste. Food waste represents the percentage of food that remains uneaten during one or more mealtimes. The amount of food waste can be influenced by food appearance, taste, and the timeliness of service. The purpose of this study was to determine the relationship between food appearance, taste, and timeliness of service with patient food waste at Dr. Abdoer Rahem Regional Hospital, Situbondo. This research employed an observational analytic design with a cross-sectional approach. A total of 50 respondents were selected using purposive sampling. The instruments used in this study included a food appearance assessment questionnaire, a food taste assessment questionnaire, a serving timeliness questionnaire, and a Comstock form. Data analysis was conducted using Fisher’s exact test with SPSS version 25. The results showed p = 0.00 for food appearance, p = 0.04 for food taste, and p = 1.00 for timeliness of service. It can be concluded that there is a significant relationship among food appearance, food taste, and food waste. At the same time, there is no significant relationship between serving timeliness and food waste. Efforts are needed to improve the taste and appearance of hospital food to reduce the high level of patient food waste. Keywords: food appearance, food waste, serving timeliness, taste